2013
DOI: 10.1021/cb300653v
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small-Molecule Enhancers of Reactive Oxygen Species That are Nontoxic or Cause Genotype-Selective Cell Death

Abstract: Elevation of reactive oxygen species (ROS) levels has been observed in many cancer cells relative to nontransformed cells, and recent reports have suggested that small-molecule enhancers of ROS may selectively kill cancer cells in various in vitro and in vivo models. We used a high-throughput screening approach to identify several hundred small-molecule enhancers of ROS in a human osteosarcoma cell line. A minority of these compounds diminished the viability of cancer cell lines, indicating that ROS elevation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…Departments of 1 Biological Engineering and 2 Chemical Engineering, Massachusetts Institute of Technology, Cambridge, Massachusetts.…”
Section: Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Departments of 1 Biological Engineering and 2 Chemical Engineering, Massachusetts Institute of Technology, Cambridge, Massachusetts.…”
Section: Innovationmentioning
confidence: 99%
“…Given the role of GSH in the reduction of H 2 O 2 and the oxidation of sulfhydryl group, it is believed that GSH depletion will cause toxicity via accumulation of H 2 O 2 and oxidized proteins (6). It has been previously suggested that electrophilic small molecules such as buthionine sulfoximine (BSO), piperlongumine (PL), and phenethyl isothiocyanate (PEITC) convey at least part of their toxicity via this mechanism (9,16,39,49,51,56), and all of these drugs have been shown to be selectively toxic to certain in vitro and in vivo tumor models (1,5,13,39). Incubation of tumor cells with piperlongumine and PEITC results in depletion of GSH and elevation of fluorescence from dichloro-dihydro-fluorescein diacetate (DCFH-DA), a cell permeable dye that exhibits increasing fluorescence intensity upon oxidation (9,39,49,56).…”
Section: Innovationmentioning
confidence: 99%
“…Therefore, the tightly balanced oncogenic redox system is presenting an attractive target for novel anticancer therapies (8)(9)(10). However, as solely increasing oxidative stress to induce cancer cell death seems to be insufficient (11), other strategies to target the cancer-specific redox environment might be more effective.…”
Section: Introductionmentioning
confidence: 99%
“…Piperlongumine has multiple pharmacologic activities: it has been described as a platelet aggregation inhibitor (3), an anxiolytic agent (4), an antidepressant (5), an antinociceptive agent (6), an anti-atherosclerotic agent (7), an antidiabetic agent (8), an anti-inflammatory agent (9), and an infectious pathogen inhibitor (10). Furthermore, piperlongumine has been reported to kill multiple types of cancer cells, inhibit metastasis, and have antitumor activities in a variety of animal models (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%